Congestion. Rationalising Automobility in the Face of Climate Change. - Lindegaard, Laura Bang (Lang, 2015)
The book investigates the negotiation of governmental rationalities of car-dependent life in the face of climate change. It appears that current forms of governing are bound up with a specific utilisation of the freedom of the governed. Accordingly, the book demonstrates how the governing of automobility unfolds as people account for and, hence, conduct their transportation practices. In this way, it unravels how villagers in a small Danish village negotiate a municipal strategy and conduct their transportation practices in ways that merely sustain the villagers' already maintained car-dependent life forms.
Keywords: Individualverkehr; Autoverkehr; Mobilität; Verkehrsaufkommen; Verkehrsbelastung; Straßenbelastung; Mobilitätsverhalten; Governance; Rationalität; Verkehrsstau; Empirische Untersuchung